On MKC-Spaces, MLC-Spaces and MH-Spaces - Delfi Ali, Reyadh; Abdulla Abker, Adam (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The purpose of this paper is deal with the study of -spaces( spaces whose minimal spaces) and ( spaces whose minimal )also we studied the relationships between minimal spaces, minimal and minimal Hausdroff spaces.